Combining Polymer and Cyclodextrin Strategy for Drug Release of Sulfadiazine from Electrospun Fibers - Morais, Diego C.; Fontes, Marina L.; Oliveira, Analú B. [UNESP]; Gabbai-Armelin, Paulo R. [UNESP]; Ferrisse, Túlio M. [UNESP]; De Oliveira, Luiz F. C.; Brighenti, Fernanda Lourenção [UNESP]; Barud, Hernane S.; De Sousa, Frederico B. (My University, 2023)
This study reports the fabrication of polymeric matrices through electrospinning using polymethyl methacrylate (PMMA) and poly(lactic-co-glycolic acid) (PLGA), biocompatible polymers commonly used in medical systems. These polymers were combined with an antibacterial drug, sulfadiazine sodium salt (SDS) or its supramolecular system formed with hydroxypropyl-β-cyclodextrin (HPβ/CD) at 1:1 molar ratio, aiming to assemble a transdermal drug delivery system. The formation of fibers was confirmed by scanning electron microscopy (SEM), and the fibers’ surface properties were analyzed using contact angle and water vapor permeability techniques. Drug release tests and cell viability assays were performed to evaluate the potential toxicity of the material. SEM images demonstrated that the obtained fibers had nanoscale- and micrometer-scale diameters in PLGA and PMMA systems, respectively. The contact angle analyses indicated that, even in the presence of hydrophilic molecules (SDS and HPβCD), PMMA fibers exhibited hydrophobic characteristics, while PLGA fibers exhibited hydrophilic surface properties. These data were also confirmed by water vapor permeability analysis. The drug release profiles demonstrated a greater release of SDS in the PLGA system. Moreover, the presence of HPβCD improved the drug release in both polymeric systems and the cell viability in the PMMA SDS/HPβCD system. In terms of antibacterial activity, all membranes yielded positive outcomes; nevertheless, the PLGA SDS/HPβCD membrane exhibited the most remarkable results, with the lowest microbial load values. Additionally, the pseudo wound healing analysis demonstrated that the PLGA SDS/HPβCD fiber exhibited results similar to the control group. Consequently, these findings exemplify the substantial potential of the obtained materials for use in wound healing applications.
Keywords: drug delivery; electrospinning; in vitro; nanomaterials; supramolecular systems